2006
DOI: 10.1111/j.1743-6109.2006.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a porcine incisional wound model and novel scarring scales

Abstract: A major goal of wound management is to reduce scarring. Prior to evaluating novel anti-scarring therapies, we developed a porcine incisional wound model and scarring outcome measures. Forty-eight full-thickness incisions (3 cm in length) and excisional wounds (3 x 0.5 cm) were created on two animals and closed with sutures (n=24) or tissue adhesive (n=24). Scars were evaluated using two validated clinical scar scales and a novel scale developed for animals. Full-thickness biopsies were obtained at 5 and 8 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The collagen fibers were viewed under normal as well as polarized light. 14 Apoptosis was identified from immunohistochemical staining, and apoptotic zones were defined as areas with more than 10 percent of cells staining positively for apoptosis. The depth of the beginning and end of these zones was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The collagen fibers were viewed under normal as well as polarized light. 14 Apoptosis was identified from immunohistochemical staining, and apoptotic zones were defined as areas with more than 10 percent of cells staining positively for apoptosis. The depth of the beginning and end of these zones was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Scar Surface Area Photographs of each wound were taken before the full-thickness excision biopsy ( Figure 3A) and after fixation of the biopsy with formalin ( Figure 3B). 21 ImageJ software (National Institute of Health, Bethesda, MD) was used to calculate the total surface area of the scar (in square centimeter).…”
Section: Measures and Outcomesmentioning
confidence: 99%
“…(2002a,b) showed that the zeroth‐order maximum of Fourier analysis can be used reliably for determining the orientation of the collagen bundles and that it is a valid measurement method for this purpose. Fourier analysis has been widely applied to determine the orientation of structures and, besides using it for the objective assessment of collagen orientation in diseased skin and scars (van Zuijlen et al , 2002a,b; Har‐Shai et al , 2003; van Zuijlen et al , 2003; Ng et al , 2005; Har‐Shai et al , 2006; Singer & McClain., 2006,), it has been used to quantify the orientation of structures in other types of tissue, such as ligaments (Chaudhuri et al , 1987), the annulus fibrosus (Guerin & Elliott, 2006) and vascular endothelial cells (Palmer & Bizios, 1997).…”
Section: Introductionmentioning
confidence: 99%